Connected Viewing : Selling, Streaming, & Sharing Media in the Digital Age. - Holt, Jennifer (Taylor and Francis, 2013)
As patterns of media use become more integrated with mobile technologies and multiple screens, a new mode of viewer engagement has emerged in the form of connected viewing, which allows for an array of new relationships between audiences and media texts in the digital space. This exciting new collection brings together twelve original essays that critically engage with the socially-networked, multi-platform, and cloud-based world of today, examining the connected viewing phenomenon across television, film, video games, and social media. The result is a wide-ranging analysis of.